IMPLEMENTASI HAK PEKERJA DALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL - Hanggoro Prabowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
The workers' right are regional minimum wages, the rational working facilities, social insurance, Working health insurance, standard for overtime wages, unemployment compensation according to Man Power Departemen and The Man Power Legislation 2003.The Industrial Affairs Solution Dispute according to The Man Power Legislation 2003 needs 3 years. Mean while 4 years for PPHI Legislation. The principle for Industrial Affairs Solution executed by businessmen, workers or worker union in discussion for agreement. In Bipatride's failure, it could be used mediation, consolation, and arbriter. The last effort on the hand of Industrial affairs solution in the state court. But the best way is the parties to solusi the problem by theirselver, impartial and the mutual gaining.